Successive Factor VIII Doses for a Haemophiliac Undergoing Major Surgery Calculated on a Microcomputer - Duncan, Bruce; Lloyd, John; Lesnikowski, Elizabeth (Thrombosis and Haemostasis, 1982)
Doses of factor VIII to be infused into a haemophiliac undergoing major surgery were calculated on a micro-computer. The degree to which the particular patient responded to infused factor VIII and the rate at which it decayed were estimated by two pre-operative experiments. Plasma levels of factor VIII were predicted over fourteen days during which time the patient was infused with 53,000 iu. A continuous plot of predicted values with time was displayed on a video monitor. The predicted values showed good agreement with assay results.
Keywords: Haemophilia; Factor VIII; Computer; Surgery